2014
DOI: 10.1007/s10658-014-0460-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic and virulence variability of Stemphylium lycopersici associated with leaf spot of vegetable crops

Abstract: Stemphylium lycopersici (Enjoji) W. Yamam was initially described from tomato and has been reported to infect different hosts worldwide. Sequence analyses of the internal transcribed spacer (ITS) regions 1 and 2, including 5.8S rDNA (ITS-5.8S rDNA) and glyceraldehyde-3-phosphate dehydrogenase (gpd) gene, random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR), as well as virulence studies were conducted to analyze 46 S. lycopersici isolates. Stemphylium lycopersici isolates used in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
2
36
0
1
Order By: Relevance
“…Our current findings were consistent with those of previous studies on A. alternata isolates obtained from citrus hybrids [23], potato plants [10,24], and tomato plants [24,25] throughout Iran. The RAPD and ISSR techniques are extremely powerful tools for distinguishing among individuals that exhibit intraspecific and interspecific variability [26]. In the present study, 100% and 84% of the isolates were found to be polymorphic with respect to the RAPD and ISSR markers, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…Our current findings were consistent with those of previous studies on A. alternata isolates obtained from citrus hybrids [23], potato plants [10,24], and tomato plants [24,25] throughout Iran. The RAPD and ISSR techniques are extremely powerful tools for distinguishing among individuals that exhibit intraspecific and interspecific variability [26]. In the present study, 100% and 84% of the isolates were found to be polymorphic with respect to the RAPD and ISSR markers, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…All isolates were collected from the MR219 rice variety, which is the most popular variety of rice planted on 70% of all rice plantation areas in Malaysia (Hashim et al 2015), and recently it has shown signs of being susceptible to the rice blast disease. Although the results of RAPD analysis showed quite good congruence with the results obtained from ISSR studies, a greater effective ratio of multi-locus Table 1 Coefficient doi: 10.17221/102/2016-CJGPB markers as well as a higher number of private alleles were observed using ISSR markers (Nasehi et al 2014). (Mishra et al 2006), Korea (Park et al 2003), China (Ngueko et al 2004), Iran (Javan-Nikkhah et al 2004 and India (Chadha & Gopalakrishna 2005), which is in agreement with the findings of this study.…”
Section: Discussionsupporting
confidence: 55%
“…Because of the low precision and overlapping of some morphological characteristics, more accurate methods such as DNA sequencing have been employed to identify fungal pathogens (Nasehi et al 2014). In this respect, the use of molecular techniques such as sequencing of different regions of DNA is considered as alternatives to morphological methods of identification of Magnaporthe species (Hirata et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations